Modelling the carding of recycled carbon fibre - Roberts, J (2023)
Carbon fibre is a very versatile material with applications in many different industries from medical, electronics, marine, to space. The demand for carbon fibre composites is increasing yearly and therefore the amount of waste carbon fibre is rising. This waste can be recovered and turned into a material that can be used in industry. The waste carbon fibre is converted into a “nonwoven” form using a carding process. This is carried out in a carding machine, with the aim of producing a homogeneous web of aligned fibres.